Radiation in Combination With Targeted Agents and Immunotherapies for Pediatric Central Nervous System Tumors - Progress, Opportunities, and Challenges - Qiu, Bo; Kline, Cassie; Mueller, Sabine (Frontiers in Oncology, 2021)
Pediatric brain tumors are the most common solid tumors in children and represent a heterogenous group of diagnoses. While some are treatable with current standard of care, relapsed/refractory disease is common and some high-risk diagnoses remain incurable. A growing number of therapy options are under development for treatment of CNS tumors, including targeted therapies that disrupt key tumor promoting processes and immunotherapies that promote anti-tumor immune function. While these therapies hold promise, it is likely that single agent treatments will not be sufficient for most high-risk patients and combination strategies will be necessary. Given the central role for radiotherapy for many pediatric CNS tumors, we review current strategies that combine radiation with targeted therapies or immunotherapies. To promote the ongoing development of rational combination treatments, we highlight 1) mechanistic connections between molecular drivers of tumorigenesis and radiation response, 2) ways in which molecular alterations in tumor cells shape the immune microenvironment, and 3) how radiotherapy affects the host immune system. In addition to discussing strategies to maximize efficacy, we review principles that inform safety of combination therapies.